Soft displaced leptons at the LHC - Blekman, Freya; Desai, Nishita; Filimonova, Anastasiia; Sahasransu, Abanti Ranadhir; Westhoff, Susanne (Journal of high energy physics, 2020)
Soft displaced leptons are representative collider signatures of compressed dark sectors with feeble couplings to the standard model. Prime targets are dark matter scenarios where co-scattering or co-annihilation sets the relic abundance upon freeze-out. At the LHC, searches for soft displaced leptons are challenged by a large background from hadron or tau lepton decays. In this article, we present an analysis tailored for displaced leptons with a low transverse momentum threshold at 20 GeV. Using a neural network, we perform a comprehensive analysis of the event kinematics, including a study of the expected detection efficiencies and backgrounds at small momenta. Our results show that weak-scale particles decaying into soft leptons with decay lengths between 1 mm and 1 m can be probed with LHC Run 2 data. This motivates the need for dedicated triggers that maximize the sensitivity to displaced soft leptons.
Gesehen am 14.01.2021